Comparative validation of automated perfusion analysis software for ischemic penumbra estimation and EVT decision-making - Kim, Jonguk; Park, Jong-Hyeok; Kim, Dongmin; Lee, Myungjae; Kim, Joon-Tae; Sunwoo, Leonard; Jung, Cheolkyu; Ryu, Wi-Sun; Kim, Beom Joon (Frontiers in Neuroscience, 2025)
BackgroundWhile computed tomography perfusion is widely used in acute stroke imaging, magnetic resonance perfusion-weighted imaging (PWI) offers superior spatial resolution and tissue specificity, particularly when combined with diffusion-weighted imaging (DWI). However, no prior study has systematically compared automated PWI analysis platforms. This study aims to evaluate the performance of a newly developed software (JLK PWI) against the established RAPID platform in terms of volumetric agreement and clinical decision concordance.MethodsThis retrospective multicenter study included 299 patients with acute ischemic stroke who underwent PWI within 24 h of symptom onset. Volumetric agreement between RAPID and JLK PWI was assessed using concordance correlation coefficients (CCC), Bland–Altman plots, and Pearson correlations. Agreement in endovascular therapy (EVT) eligibility was evaluated using Cohen’s kappa based on DAWN and DEFUSE-3 criteria.ResultsThe mean age was 70.9 years, 55.9% were male, and the median NIHSS score was 11 (IQR 5–17). The median time from the last known well to PWI was 6.0 h. JLK PWI showed excellent agreement with RAPID for ischemic core (CCC = 0.87; p < 0.001) and hypoperfused volume (CCC = 0.88; p < 0.001). EVT eligibility classifications based on DAWN criteria showed very high concordance across subgroups (κ = 0.80–0.90), and substantial agreement was observed using DEFUSE-3 criteria (κ = 0.76).ConclusionJLK PWI demonstrates high technical and clinical concordance with RAPID, supporting its use as a reliable alternative for MRI-based perfusion analysis in acute stroke care.